Perhitungan Neraca Massa Pada Unit Screw Press di PT. XYZ - Novia Nelza (JURNAL VOKASI TEKNIK, 2023)
Function of screw press is for extraction or separate crude oil from mesocarp based on mechanical. In extraction process based on mechanical all the mass out from digester will be extraction on unit is named screw press with capacity 12 ton/hour. In extraction process is added dillution water 9% from capacity process. This study aims to calculate mass in and out from screw press. The method is used calculating of mass balance. The mass balance is a calculation of all the materials that enter, accumulate and leave a system within a certain time. For the result of mass balance flow mass enter on screw press such as mass out from digester is 8,0604 ton/hour dan dilution water is 1,08 ton/hour. While flow mass out of screw press dregs of press is 2,352 ton/hour dan crude palm oil is 6,7884 ton/hour.